Medical student learning on a distributed training platform in rural district hospitals - Andrew J. Ross; Thandaza C. Nkabinde; Bernhard Gaede (AOSIS, 2024)
Background: Decentralising medical school training enhances curriculum relevance, exposing students to generalist patient care in diverse contexts. Aim: The aim of the study was to understand the student experiences of learning during their 7-week Family Medicine rural rotation. Setting: Final year medical students who had completed their Family Medicine rotation in November 2022. Methods: A qualitative study involving 24 final year students (four semi- structured interviews and four focus group discussions [4 x 5 students]). All interviews were recorded, transcribed verbatim and analysed thematically. Results: Analysis revealed positive learning experiences and identified the following themes: taking responsibility for learning, the generalist context, teaching and learning in context and managing the learning environment. Conclusion: Active participation in hospital activities, exposure to disorientating dilemmas that challenged assumptions and reflection on these experiences led to transformative learning and knowledge co-construction. Contribution: The study contributes to the discussion and reinforces the advantages of distributed, experiential training, highlighting the positive impact of meaningful participation and transformative learning opportunities.